2009
DOI: 10.1002/bdd.653
|View full text |Cite
|
Sign up to set email alerts
|

Transport characteristics of L‐citrulline in renal apical membrane of proximal tubular cells

Abstract: L-Citrulline has diagnostic potential for renal function, because its plasma concentration increases with the progression of renal failure. Although L-citrulline extracted by glomerular filtration in kidney is mostly reabsorbed, the mechanism involved is not clearly understood. The present study was designed to characterize L-citrulline transport across the apical membranes of renal epithelial tubular cells, using primary-cultured rat renal proximal tubular cells, as well as the human kidney proximal tubular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Transplacental transport of citrulline is not well characterized. In the rat small intestine and the apical membrane of renal proximal tubular cells, citrulline transport appears to occur via Na + -dependent systems [40, 41]. IUGR is associated with elevated levels of maternal arginine [42], but intracellular arginine and citrulline are reduced in human umbilical vein cells (HUVECs) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental transport of citrulline is not well characterized. In the rat small intestine and the apical membrane of renal proximal tubular cells, citrulline transport appears to occur via Na + -dependent systems [40, 41]. IUGR is associated with elevated levels of maternal arginine [42], but intracellular arginine and citrulline are reduced in human umbilical vein cells (HUVECs) [39].…”
Section: Discussionmentioning
confidence: 99%
“…There are sodium-independent transporters in the nervous system (26) and sodium-dependent transporters in rat endothelial cells (33). In the kidney, Mitsuoka et al (19) identified B(0)AT1 and b(0,ϩ)AT, sodiumindependent and -dependent transporters of citrulline on the apical membrane of cultured rat renal proximal tubular cells. On the basolateral side of the proximal tubules, sodiumindependent transporters are present and OAT1 is the primary basolateral transporter (22).…”
Section: Discussionmentioning
confidence: 99%
“…34 Yet, in studies with rat renal proximal tubular epithelial cells and the human kidney proximal tubular epithelial cell line, HK-2, apical uptake of L-citrulline was shown to be mediated by at least two distinct Na + -dependent transport systems and one Na + -independent transport system. 35 Likewise, studies with Caco-2 cells, a model of human intestinal epithelial cells, found that apical L-citrulline uptake was mediated both by Na + -dependent (via System B (0,+) ) and Na + -independent (via Systems Figure 5 Citrulline uptake in PAECs cultured under normoxic and hypoxic conditions for 24, 48, or 72 h: (A) total uptake; (B) System A-mediated uptake (determined by the use of amino acid competitors to select for System A: glutamine, histidine, threonine, and leucine, amino acids preferentially transported by Systems N, ASC, and L, respectively); (C) System N-mediated uptake (determined by the use of amino acid competitors to select for System N: 2-methylaminoisobutyric acid, leucine, and threonine, amino acids preferentially transported by Systems A, L, or ASC, respectively). All studies were performed in triplicate using PAECs from three to four different piglets.…”
Section: Figure 4 (A -D)mentioning
confidence: 99%